Tingkat Pemahaman Inflasi Mata Uang di Kalangan Gen-Z Studi Kasus di Kecamatan Gondanglegi Malang (Jurnal Kendali Akuntansi, 2025)
Inflation is a condition in which the economy is marked by a general and continuous increase in the prices of goods and services over a certain period. Inflation reflects a decrease in the purchasing power of money due to the rising prices of goods and services. This study aims to analyze the level of understanding of inflation among Generation Z in Gondanglegi District, Malang Regency. Inflation is a crucial economic indicator that affects purchasing power and decision-making, particularly for the younger generation growing up in a dynamic economic landscape.The research uses a qualitative approach with data collected through Google Forms and strengthened with interview data. Respondents were 50 individuals aged between 19 and 25 years, all of whom had graduated from high school (SMA). The data were analyzed descriptively to understand the depth of knowledge and perception of inflation among these individuals.The results indicate that while most respondents are familiar with the term "inflation," their understanding of the causes, impacts, and ways to mitigate it is still superficial. Factors such as educational background, access to digital economic content, and daily economic experiences influence their level of understanding. This study contributes to the development of targeted economic literacy programs for Gen-Z.